A comparison of carcass characteristics and meat quality in goats subjected to pre-slaughter head-only electrical stunning and slaughter without stunning - Lokman, Nur Sakinah (2016)
Stunning method that most widely used in small ruminants was electrical stunning system. Based on the electrophysiological evidence, the stimulation of the brain results in unconsciousness and insensibility in animals while the stunned animals may not experience unnecessary pain and distress during slaughter. The head-only electrical stunning (HOES) method has been accepted for the halal market. However, it has been shown to have adverse effects on carcass and meat quality which become the main problem in the industry. Visual carcass defects such as haemorrhages (i.e., speckles) are among the drawbacks related to carcass characteristics. Meanwhile, haemorrhages are not usually encountered in slaughter without any form of stunning (i.e., traditional halal slaughter (NS)). Thus, this study was conducted with the aim to determine the effects of HOES and NS method on carcass characteristics and meat quality assessment in goats. 12 male Boer crossbred goats were used in this study. The goats were divided into two groups of 6 animals each. In the first group, animals were NS according to the traditional halal slaughter procedure while the second group of goats were subjected to pre-slaughter HOES. Meat quality traits such as pH, water holding capacity, colour, tenderness, MFI and sarcomere length were determined on semitendinosus (ST) muscle, while the incidences of blood splash were morphologically examined on shoulders and legs of each carcass. The present results indicate no differences (p>0.05) in meat quality traits examined between the treatments. However, higher incidence of hemorrhages were observed on carcass of HOES animals than those NS. Thus, this study affirms that electrical stunning prior slaughter increased carcass hemorrhages without adversely affecting meat quality traits.